Protection of property through waqf institution: analysis of court decision in Malaysia pre and post-independence - Mohamad, Nor Asiah (International Islamic University Malaysia, 2019)
This article examines court decision pertaining to Waqf: Pre and Post Independence. It shows the influence of English law of Trust on Waqf Evolution in Malaysia.